DIFFICULTIES IN TEACHING FOREIGN LANGUAGES TO YOUNG LEARNERS - Kohorova Mohichehra; Jalolova Muqaddas (TADQIQOTLAR, 2025)
Annotation: This article explores the complex challenges teachers face when teaching foreign languages to young learners. It focuses on key issues such as cognitive limitations,  emotional  sensitivity,  overuse  of  the  native  language,  individual differences in learning styles, and limited exposure outside the classroom. The article emphasizes the importance of using age-appropriate, culturally relevant materials and fostering a supportive learning environment. It also discusses the role of parents and how  their  expectations  can  impact  the  learning  process.  Practical  suggestions  are provided  to  help  teachers  create  more  effective  and  engaging  lessons  for  young language learners.